2018
DOI: 10.1088/1475-7516/2018/03/019
|View full text |Cite
|
Sign up to set email alerts
|

The full-sky relativistic correlation function and power spectrum of galaxy number counts. Part I: theoretical aspects

Abstract: We derive an exact expression for the correlation function in redshift shells including all the relativistic contributions. This expression, which does not rely on the distantobserver or flat-sky approximation, is valid at all scales and includes both local relativistic corrections and integrated contributions, like gravitational lensing. We present two methods to calculate this correlation function, one which makes use of the angular power spectrum C (z 1 , z 2 ) and a second method which evades the costly ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 70 publications
0
88
0
Order By: Relevance
“…A detailed analysis of the correlation function was performed in [36]. The bottom left panel of fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A detailed analysis of the correlation function was performed in [36]. The bottom left panel of fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We also use the standard plane-parallel approximation, which is reasonable on ultra-large scales. However, we note that wide-angle effects in the power spectrum can be of the same order of magnitude as the Doppler-type effects in certain circumstances (Tansella et al 2018), and these should be incorporated in a more complete treatment.…”
Section: Relativistic Contributions To the Galaxy Bispectrummentioning
confidence: 96%
“…Studies of nonlinear gravitational effects have also shown that energy from small-scale gravitational interactions can have a considerable impact on the cosmological properties of a spacetime [3,4]. Even within a standard perturbative cosmological framework, it has been shown that neglected relativistic effects can lead to percent-level or larger corrections when computing observables [5][6][7], providing a means by which we can study general relativity beyond its dominant behavior.…”
Section: Introductionmentioning
confidence: 99%